EVALUATING THE DIAGNOSTIC UTILITY OF DIFFUSION WEIGHTED IMAGING COMPARED TO DCE MRI IN DETECTION OF BREAST PATHOLOGY (The Research of Medical Science Review, 2025)
To estimate diagnostic utility of Diffusion Weighted Imaging compared to DCE MR in detection of breast pathology. Research design: Analytical cross sectional study. Research settings: Department of Radiology, Islamabad Diagnostic Center, Faisalabad, from October 2024 to December 2024. Method: MRI breast scan was performed on 89 patients having breast pathologies, and complain related to breast according to the inclusion criteria. Breast lesions were characterized into BIRADS classification based on diffusion restriction and contrast enhancement. Histopathology was considered gold standard to characterize lesions into neoplastic and non- neoplastic categories. We calculate the Sensitivity, specificity, positive and negative predictive values and diagnostic accuracy of DWI and DCE-MRI .Correlations of DWI and DCE-MRI was done with histopathology.Results: DWI had a sensitivity 92.6%, specificity 88.6%, positive predictive value 89.89%, negative predictive value 90.74%, diagnostic accuracy 88.57% in detection of breast lesions while DCE-MRI had sensitivity 92.6%, specificity 77.1%, positive predictive value 86.2%, negative predictive value 87.1%, diagnostic accuracy 86.5%. Significant correlation was found between DWI and histopathology and DCE-MRI and histopathology. P-value of 0.000 was calculated. Conclusion: DWI and DCE MRI are two best methods of breast lesion detection. Sensitivity of both these techniques are comparable but DWI offers superior specificity with less false positive results. DWI also being slightly more good at diagnostic accuracy.